A novel Delay-Based Multicast Routing Protocol in ad hoc wireless networks. (24th June 2011) - Hsu, Wu-Hsiao; Chen, Jenhui; Yeh, Sheng-Cheng
This paper proposes a Delay-Based Multicast Routing Protocol (DBMRP) for multicast transmissions in ad hoc wireless networks. The DBMRP uses an on-demand, source-based multicast routing protocol, which is based on the tree forwarding methodology. The queuing delay and link delay of each visited mobile node are used to establish the multicast tree. In addition, DBMRP selects Displacement Nodes (DNs) to reduce the number of control packets when establish the multicast tree. Simulation results demonstrate that DBMRP exhibits good throughput at low mobility, and has the smallest control overhead, which results in better end-to-end delays, as compared to other algorithms.